PENGARUH PENGETAHUAN PERPAJAKAN, PELAYANAN FISKUS, SANKSI PAJAK, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KOTA SURAKARTA - Indri Ramadhanti; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
Tax is one of the country's acceptance resources to promote national development and a source of financing for development in the welfare of the community. The purpose of the study is to know (1) the influence of taxation knowledge on UN taxpayer compliance (2) The influence of fisial service to UN taxpayer compliance (3) Effect of tax sanctions on PB taxpayer compliance, (4) influence Socialization of taxation on UN taxpayer compliance. This research uses primary data in the form of questionnaires given to respondents in five sub-districts in Surakarta. The population in this study was 124,720 taxpayers in Surakarta. The sampling techniques in this study used the Sampling cluster method. The data analysis techniques used in this study are descriptive analysis, instrument test, classical assumption test, double linear regression analysis, coefficient of determination test, T test and F test. The result of the count-1.716 with a P-value of 0.090 > 0.05 means no negative influence and no significant taxation knowledge (X1) to the taxpayer's compliance (Y). The result of a count-0.720 with a P-value of 0.473 > 0.05 means there is a negative influence and insignificant Fischus service (X2) against taxpayer compliance (Y). The result of the 3.605 calculated with a P-value of 0.000 < 0.05 means there is a positive and significant influence on tax sanctions (X3) against taxpayer (Y) compliance. The result of the count-0.482 with P-value 0.631 > 0.05 means there is a negative and insignificant socialization of taxation (X4) against taxpayer compliance (Y). The result of a count-0.482 with a P-value of 0.631 > 0.05 means there is a negative influence and no significant socialization of taxation (X4) against taxpayer compliance (Y). The results of the test F 4.116 with the P-value of 0.004 < 0.05 which means simultaneously the variables of taxation knowledge (X1), Fischus Service (X2), tax sanctions (X3), and socialization of taxation (X4) have a significant effect on compliance with taxpayers in paying the Earth tax and price (Y). Test determinations indicate the Adjusted value of R Square 0.112 concluded that the taxpayer variables can be explained by the four independent variables i.e. taxation knowledge, Fischus services, tax sanctions, and socialization of taxation Other causes outside the model.